2023
DOI: 10.7717/peerj.14783
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of rice YABBY gene family: evolution, expression and interacting proteins analysis

Abstract: As plant-specific transcription regulators, YABBYs are involved in plant growth, development and stress responses. However, little information is available about genome-wide screening and identification of OsYABBY-interacting proteins. In this study, phylogenetic relationship, gene structure, protein structure and gene expression profile of eight OsYABBYs were carried out, all of which indicated that OsYABBYs were involved in different developmental processes and had functional differentiation. More importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…7 ( YAB1 ) affect both meristem, leaf, and floral development in rice (Toriba et al., 2007) and the NAC transcription factor, NAC111 , on chr. 10 (Y. Fang et al., 2008; T. Zhang et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…7 ( YAB1 ) affect both meristem, leaf, and floral development in rice (Toriba et al., 2007) and the NAC transcription factor, NAC111 , on chr. 10 (Y. Fang et al., 2008; T. Zhang et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…As members of a TF family, YABBY genes have been investigated in many species; for example, six members have been found in A. thaliana [56,57], eight in rice [37,40], nine in tomato [58], thirteen in maize [59], twenty-one in wheat [38,39], seventeen in soybean [52], seven in grapevine (Vitis vinifera) [60], twelve in Gossypium arboreum [55], and ten in Juglans regia [61]. In this study, we identified 12 CqYAB genes in quinoa.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these genes are responsible for maintaining the proper activity of the meristem [31,36]. YABBYs were also found in rice, maize, and wheat [37][38][39][40] and found functioning in carpel specification and leaf midrib formation [41], the development of vasculature [42], the determination of the fate of abaxial cells in leaf development and architecture [43][44][45], lateral organ development and meristem maintenance in spikelet [46][47][48], seed shattering [49,50], and the regulation of gibberellin metabolism [51]. Recently, a few studies have shown that YABBY genes are involved in abiotic stress responses, such as salt and drought stresses [52,53], cadmium (Cd) stress [54], and cold and heat stresses [55].…”
Section: Introductionmentioning
confidence: 99%
“…In other eudicots and fleshy fruit species, nine YABBY genes have been identified both in tomato (Solanum lycopersicum) (Han et al 2015) and in pineapple (Ananas comosus) (Li et al 2019), seven in mango (Mangifera indica) (Xia et al 2022), six in pomegranate (Punica granatum) (Zhao et al 2020), and 59 in several cucurbit species (Yin et al 2022). Moreover, YABBY genes have also been studied in monocots species including the identification of eight genes in rice (Oryza sativa) (Toriba et al 2007;Zhang et al 2023), 21 in wheat (Triticum aestivum) (Buttar et al 2020), 13 in corn (Zea mays) (Strable et al 2017), and eight in foxtail millet (Setaria italica) (Jie et al 2022). Luo et al (2022) named the YABBY genes in F. 9 ananassa from YAB1 to YAB25 and performed transcriptional analyses of eight FaYABs in green and red fruits, showing differential expression levels between these two fruit stages in four genes (Luo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…2007; Zhang et al . 2023), 21 in wheat ( Triticum aestivum ) (Buttar et al . 2020), 13 in corn ( Zea mays ) (Strable et al .…”
Section: Introductionmentioning
confidence: 99%